قرآن اور بائبل میں عورت کو جنسی استحصال سے محفوظ رکھنے کیلئے مشترکہ تعلیمات :تقابلی جائزہ: A comparative study of common teachings in the Qur’an and the Bible to protect women from sexual exploitation. - Dr: Aurangzeb (AL-IDRAK JOURNAL, 2022)
In all civilized societies in human history, chastity and good character are appreciated and obscenity is considered bad. In order to save the society from pornography and move on the path of pure peace, many ways are being considered in the world to prevent the increasing sexual crimes. How to prevent humanity from immorality and pornography? Christianity and Islam are the world's major religions with more than half the world's population if the common teachings in these religions on the prevention of immorality and adultery include Women who live in permanent homes, in the veil, and if they are old enough to marry, should marry the right person and follow their husbands and finally, to protect the mind from pornography, to this end, the Qur'an and the Bible also mention the punishments for adultery to avoid adultery. It is hoped that sexual misconduct will be curbed by exposing chastity, marriage and severe punishment for adultery at all levels and spreading awareness among the people through all government-sponsored educational institutions and media.